Monitoring electric power wheelchair battery consumption level via mobile / Ahmad Afiq Ahmad Shaiful, Romiza Md Nor and Huzaifah A Hamid - Ahmad Shaiful, Ahmad Afiq; Md Nor, Romiza; A Hamid, Huzaifah (UiTM Cawangan Perlis, 2020)
Nowadays, power wheelchair is one of the most important vehicles for people with physical disabilities such as paralysis, stroke, handicap and many more. Electric wheelchair which is also called electric-power wheelchair or powerchair can be moved by an electrically based power source, regularly motor or batteries. It is very important to have frequent monitoring battery level because power wheelchair need sufficient battery level for it to be moved around. Therefore, this project is developed to monitor the battery consumption level and real time battery monitoring. Current sensor is used to measure the current state of the battery level. In this project, Internet of Things (IoT) concept is applied where sensor and mobile application is integrated and known as BLife. Blife was designed using the visibility of the system status principles which consist of knowledge is power, appropriate feedback, compel user to action and communication creates trusts. If the battery is in the lower state, the power wheelchair users will be informed through mobile application via an indicator informing that it needs to be recharged. Moreover, the current location of the power wheelchair user is also notified to the users’ caretaker. Evaluation of Blife were conducted using functionality and usability testing based on visibility of the system status technique. Most of the respondents are satisfied and gave positive feedback. This project is a great contribution to disable people who has limited access to charge battery and to alert them on their battery level status.